Empowering Women through E-Business: A Study on Women Entrepreneurs in Dhaka City - Hossain, Tanjela (Asian Business Review, 2018)
This paper tries to evaluate the effectiveness of e-business on the empowerment of women. A survey has been administered to identify the effects of Women Entrepreneurship through e-business on Women Empowerment related attitudes. I have collected data through a semi-structured questionnaire from a sample of 100 women entrepreneurs operating online businesses located in Dhaka city. 15 employees’ personally interviewed and other 85 respondents were surveyed through e-mail and social network sites. The findings of the study indicate various factors about women empowerment. Results reveal that indicators of women empowerment are mainly (1) Economic Freedom, (2) Greater social independency & acceptability, and (3) Sense of self-worth. Twenty questions are developed to evaluate the effectiveness of e-business on the empowerment of women for mentioned three indicators. The findings of this study reveal that e-business is a powerful tool in enhancing women empowerment. Women believe that e-business is one of the easiest ways to become entrepreneur which is in turn empowering them in different social issues.